2016
DOI: 10.1177/0309324716663815
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the use of critically refracted longitudinal waves and magnetic Barkhausen noise for stress measurement in API 5L X70 steel

Abstract: According to acoustoelastic theory, ultrasonic wave velocity varies as a function of the state of stress in a body. In ferromagnetic materials, stress alters magnetic domain walls created by cyclic magnetic excitation and affects the amplitude of magnetic Barkhausen noise signals. In this work, both these properties are used to measure different levels of stress in specimens of API 5L X70 steel. Time of flight of ultrasonic critically refracted longitudinal (L cr) waves and magnetic Barkhausen noise are measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
(34 reference statements)
0
3
0
1
Order By: Relevance
“…Both the techniques were compared in terms of sensitivity and repeatability for residual stress measurement. 13) It was reported that the repeatability in ultrasonic technique is higher than magnetic barkhausen technique. Hence in this paper, ultrasonic based residual stress measurement technique (in particular Lcr Wave technique) has been used for predicting bow/crossbow in hot rolled sheets.…”
Section: Introductionmentioning
confidence: 99%
“…Both the techniques were compared in terms of sensitivity and repeatability for residual stress measurement. 13) It was reported that the repeatability in ultrasonic technique is higher than magnetic barkhausen technique. Hence in this paper, ultrasonic based residual stress measurement technique (in particular Lcr Wave technique) has been used for predicting bow/crossbow in hot rolled sheets.…”
Section: Introductionmentioning
confidence: 99%
“…It uses the variation of ultrasonic wave velocity as a function of stress level on the base of the acoustic-elastic theory. Internal stress measurement can be classified into groups according to the different type ultrasonic waves (longitudinal, transverse, longitudinally refracted and surface waves) [3][4][5][26][27][28][29][30]. The choice of NDT information parameters is difficult because of complexity of many factors such as microstructure features and stresses.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of NDT information parameters is difficult because of complexity of many factors such as microstructure features and stresses. The complicated problem has a solution by applying several NDT methods based on different physical approaches [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…MPa, o que é bastante aceitável para as principais aplicações de ensaios não destrutivos em Engenharia. Isso é verdade porque, conforme pode ser encontrado na literatura, a técnica possui resolução em torno 18 MPa para a medição de tensão (Pereira Jr, Grijalba and Santos, 2016). Além disto, a viabilidade da aplicação das equações (4.50), (4.51), (5.1), ( 5.2), (5.3) e (5.4) pode ser justificada ao ressaltar-se as particularidades no comportamento mecânico de materiais compósitos, conforme será discutido a seguir.…”
Section: Parte Analítica Modelagem E Premissasunclassified